Urethral condyloma acuminata in a male patient refractory to common topical treatments: A case report: Refractory urethral condyloma acuminata - Susetiati, Devi Artami (Journal of Pakistan Association of Dermatologists, 2022)
Condyloma acuminata is one of the most prevalent sexually transmitted diseases caused by human papilloma virus (HPV). Urethral involvement of condyloma acuminata is uncommon and more challenging to treat. Despite more condylomas are associated with the low-risk HPV (e.g., types 6 and 11), histopathologic examination is sometimes needed to exclude malignant process, especially in a lesion with atypical form or unresponsive to the standard therapy. Here we report a unique case of urethral condyloma acuminata in a male patient that refractory to the common condyloma topical treatments.